1992
DOI: 10.1161/01.str.23.12.1812
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous cerebral hypothermia diminishes focal infarction in rat brain.

Abstract: Background and Purpose: Brain temperature during ischemia is known to strongly influence the extent of cellular injury. The objectives of the present study were to determine the effect of severe focal ischemia on brain temperature and to assess the influence of those changes on focal infarction.Methods: Severe focal ischemia was produced in rats using permanent occlusion of the distal middle cerebral artery combined with transient (60-minute) bilateral carotid artery occlusion. The temperature of the ischemic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

1995
1995
2018
2018

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(21 citation statements)
references
References 27 publications
0
21
0
Order By: Relevance
“…These findings have been supported by other laboratories. Denes et al [30] reported that LPS compromised survival and increased brain edema but not infarct size as assessed by crystal-violet staining; Moyer et al [31] reported hypothermia during occlusion diminishes cerebral infarction in rats. Several groups have reported that NBQX (2,3-dihydroxy-6-nitro-7-sulfamoylbenzo (F)quinoxaline), an α-amino-3-hydroxy-5-methyl-4-isoxazole propionate antagonist, provides robust protection against neuronal loss in experimental stroke models [32][33][34][35].…”
Section: Aging and Disease • Volume 7 Number 3 June 2016 11mentioning
confidence: 99%
“…These findings have been supported by other laboratories. Denes et al [30] reported that LPS compromised survival and increased brain edema but not infarct size as assessed by crystal-violet staining; Moyer et al [31] reported hypothermia during occlusion diminishes cerebral infarction in rats. Several groups have reported that NBQX (2,3-dihydroxy-6-nitro-7-sulfamoylbenzo (F)quinoxaline), an α-amino-3-hydroxy-5-methyl-4-isoxazole propionate antagonist, provides robust protection against neuronal loss in experimental stroke models [32][33][34][35].…”
Section: Aging and Disease • Volume 7 Number 3 June 2016 11mentioning
confidence: 99%
“…Intraischemic hypothermia is most effective in transient ischemia or 'reperfusion' models (Busto et al, 1989a;Carroll and Beek, 1992;Colbourne and Corbett, 1995); the effects of intraischemic hypothermia in permanent ischemia models are far less uniform (Baker et al, 1991;Kader et al, 1992;Kozlowski et al, 1997;Lo et al, 1993;Morikawa et al, 1992;Moyer et al, 1992;Ridenour et al, 1992;Zhao et al, 2007) . In addition, it will be most meaningful clinically if hypothermia protects when applied postischemically; however, therapeutic time windows for postischemic hypothermia are limited.…”
Section: Hypothermia Does Not Always Attenuate Stroke Even In the Labmentioning
confidence: 99%
“…As little as 1 hour of moderate to deep hypothermia delayed for 1 hour after ischemia onset was beneficial in some models 16,18 but not in others. 19,25 There is no experimental evidence that brief deep hypothermia ameliorates infarct volume if initiated later than 60 minutes after onset of ischemia in permanent occlusion models. 16 Studies in other cerebral ischemia models indicate that hypothermia can protect even if cooling is delayed by several hours, provided the duration of cooling is prolonged.…”
Section: Mild Hypothermia In Models Of Pmcaomentioning
confidence: 99%